Comparative Evaluation of the Effects of Antimicrobial Photodynamic Therapy With an LED and a Laser on the Proliferation of Human Gingival Fibroblasts on the Root Surface: An In Vitro Study: Photodynamic Therapy Effect on the Proliferation of Fibroblasts - Koochaki , Mahsa; Hendi , Amirreza; Ghasemi , Mahmood; Seyedjafari , Ehsan; Hamidain, Mehdi; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2021)
Introduction: This study aimed to compare the effects of root biomodification by citric acid and antimicrobial photodynamic therapy (aPDT) with LED and laser on the proliferation of human gingival fibroblasts (HGFs). Methods: This in vitro experimental study evaluated 60 single-rooted teeth extracted due to periodontal disease. The teeth underwent scaling and root planing (SRP), and then 5 × 5 mm blocks were prepared from the cervical area of the teeth 1 mm apical to the cementoenamel junction. The blocks were divided into 4 groups (n=15 blocks): SRP alone (control), SRP + citric acid, SRP + toluidine blue (TBO) + LED light, and SRP + TBO + laser. HGFs were seeded on the surface of the samples, and the methyl thiazolyl tetrazolium (MTT) assay was performed after 24, 48, and 72 hours. Group comparisons were performed using repeated-measures ANOVA, while pairwise comparisons of the time points were performed by an LSD test. Results: Cell proliferation was higher in all experimental groups at 48 and 72 hours, compared with 24 hours (P<0.05). Cell proliferation was significantly different in the citric acid group at 24 hours (P=0.016) and 48 hours (P=0.015), compared with other groups. However, cell proliferation was not significantly different in the aPDT group with LED Photosan and a diode laser at 24 and 48 hours (P>0.05). Conclusion: aPDT and citric acid can enhance the proliferation of HGFs on dentin blocks. Further studies can pave the way for their future use in the clinical setting. DOI: 10.34172/jlms.2021.47